Rebecca Hotra: capstone - Hotra, Rebecca, artist (Colorado State University. Libraries, 2022)
The artist's statement: My tendency to daydream and escape into my favorite story or imagination as a kid is something that is still heavily reflected in my work today. As an introverted artist existing in such a fast-paced, often overwhelming world, I often like to capture a sense of light-hearted escapism within my work that I can share with others. My work's influences range wildly: from the nostalgia of pop culture and jaded ironic humor of internet culture to the whimsy and warmth of personal childhood memories-- all captured in the medium of digital illustration and design for the purpose of inviting others into that moment of light-hearted laughter and escapism. Some of my favorite stories as a kid revolved around the fantastical adventures of talking animals or the mythological interpretations of the natural world. My current focus of work revolves around developing my own animated characters that reflect this childhood passion of mine, as well as being inspired by the work of UK photographer George Kells and Hayao Miyazaki. Not only am I interested in the logistics of bridging the gap between conceptual designs to fully-realized storytelling, but I find that projects of this nature allow me to indulge in a passion for creating charming and loveable characters that I hope audiences can take comfort and joy in. I've found myself imagining the lives and adventures of the smaller creatures in our world, and so I've taken that approach to my current development of a mouse character and her bumblebee sidekick in a world much larger than her. While I keep a number of sketchbooks and pens on hand, I most often find myself reaching for my digital design tools, in both my personal and professional work. I find that the medium of digital illustration gives me a flexibility I've not experienced in other mediums, as well as the opportunity to explore a variety of options in a short amount of time. I can almost instantly draft an idea and share it with anyone but return to my work and revise it to my liking at any time, in virtually any place.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design